Continuing Professional Accounting Education in The Kurdistan Region - Iraq And Ways to Improve it - Al-Nuaimi, Basima F. (Humanities Journal of University of Zakho, 2017)
The auditing profession occupies an excellent center in the communities in general; its servings diverse - notably the auditing of financial statements - to many beneficiaries who rely on them in various fields, and the performance of these services are carried out by certified public accountants who should have the scientific and practical capacity as a prerequisite for obtaining a license to practice the profession. With the increasing need for professional accountants’ services، we find that there is a need to pay greater attention to the continuing professional accounting education because of its importance in human development in the community، through the continuous development of the skills and abilities of the professional accountants; this is due to the fact that the main roles in this profession rest on the human element، and that any desire or attempt to promote the profession، thus reinforcing its position and its importance in the community، starts through paying attention to the human element، by improving their skills to meet the challenges of increasing and accelerating pace of the modern time. This research has addressed the subject of continuing professional accounting education in order to identify the concept، its importance، its scope، the reasons that require its presence، as well as explore the reality of this continuous education in Kurdistan Region / Iraq، by testing hypotheses through a field study; the research has concluded that there is a lack of the participation factor of professional accountants in the Region in continuing professional education، because there are some obstacles، and that these obstacles can be overcome through multiple means and methods.